An operation for anomalous origin of left coronary artery. Issue 1 (January 1979) - Hamilton, D I; Ghosh, P K; Donnelly, R J
Abstract : Successful surgical correction for anomalous origin of the left coronary artery from the pulmonary artery in a 4-year-old child is reported. An aortopulmonary fistula was created and a pericardial baffle was inserted within the pulmonary artery to connect the fistula to the ostium of the left coronary artery. The clinical, haemodynamic, and angiographic features of the anomaly are presented. The child's progress is satisfactory 17 months after the operation.